Pengembangan Tes Higher Order Thinking Skills (HOTS) untuk Mengukur Keterampilan Berpikir Peserta Didik Kelas IV SD - Ariani, Dita; Kartono, Kartono; Pranata, Rio (YASIN, 2025)
The limited development of assessment instruments capable of measuring Higher Order Thinking Skills (HOTS) at the elementary school level forms the background of this study, considering the crucial role of higher-order thinking in supporting the quality of 21st-century learning. This research aims to develop a HOTS test instrument that is valid, reliable, and feasible for measuring fourth-grade students' thinking skills on the topic Ini Khas Daerahku at SDN 10 Sungai Kakap. The method employed is Research and Development (R&D) using the ADDIE model, which includes the stages of analysis, design, development, and implementation. The validation process involved subject matter experts, language experts, and construction experts, along with both limited and large-scale trials. Data were collected through validation sheets and empirical testing of the test items, then analyzed using validity, reliability, difficulty level, and discrimination index tests. The findings indicate that the developed instrument is highly feasible for use; most items are valid, the reliability is high, the difficulty level is within the ideal range, and the discrimination index reflects good quality. This study confirms that HOTS-based assessment is effective in fostering students' abilities in analysis, evaluation, and creation. The main conclusion is that the development of a locally contextualized HOTS instrument produces a measurement tool aligned with curriculum needs and supports the enhancement of competency-based learning. The research has theoretical implications for educational assessment studies and practical implications as a guide for teachers in designing contextual and 21st-century skills-oriented assessments.